In situ fabrication of cobalt/nickel sulfides nanohybrid based on various sulfur sources as highly efficient bifunctional electrocatalysts for overall water splitting - Mengqiu Li; Ze Xu; Yuting Li; Juan Wang; Qin Zhong (Nano Select, 2022)
Abstract Transition metal chalcogenides are attractive electrocatalysts for oxygen evolution reaction (OER) or hydrogen evolution reaction (HER) due to their natural abundance and diverse structure. Herein, nickel sulfides (Ni3S2) and nickel/cobalt sulfides nanohybrid have been in situ fabricated on nickel foam (NF) by a facile hydrothermal method with sodium sulfide (Ss), L‐cysteine (Lc) or thiourea (Tu) as a sulfur source, respectively. The results show that sulfur source has a great influence on the phase structure, morphology and electrocatalytic performance of transition metal sulfides. The nickel sulfide with the sodium sulfide as a sulfur source (NiSs) shows better HER and OER activity in 1 M KOH. With the Co‐doping, three‐dimensional honeycomb‐like NiCoSs nanosheet clusters exhibits the enhanced electrocatalysis properties with overpotentials of only 168 mV at 10 mA cm–2 for HER and 234 mV at 20 mA cm–2 for OER, respectively. The NiCoSs shows the good bifunctional activities for overall water splitting and presents considerable stability for 24 hours. The good electrochemical activities of metal sulfides by using inorganic sodium sulfide can be attributed to the large exposed surface area and heterostructure compositions of Co9S8 and Ni3S2.